Virtual Dressing Using Kinect Sensor (International Journal of Food and Nutritional Sciences, 2022)
A large number of online shopping websites have popped up as a resultof recent advances in web technology. Online shopping, however, hassome disadvantages in addition to its benefits. Due to the wide range inbody type, hair color, and size, it might be challenging for someone toimagine how a certain item will look on them and their skin tone, amongother things, among humans. For both the client and the trader,evaluating thefit of clothing is crucial. Our methodology focuses on howthe chosen outfit fits the user's body and how it would appear if he orshe were in the actual world. It normally takes a lot of time to try onthings in a store. Additionally, in situations like internet purchasing, itmight not even be able to try on clothing. By establishing a virtualchanging room setting, we hope to improve accessibility and timeefficiency for trying on clothing. The installed system offered a cuttingedgetechnique that is presented for the purchase of apparel through avirtual try-on platform. This process takes a great deal less time than thestandard procedure, making it simpler for both the vendor and thebuyer. This offers a plausible behavior for the appropriateness of thegarment's details. Theentire process begins with a webcam image of theuser, which immediately creates the ambiance of a virtual dressingroom.